2019
DOI: 10.37358/mp.20.2.5373
|View full text |Cite
|
Sign up to set email alerts
|

Composite Resins - Multifunctional Restorative Material and Practical Approaches in Dental Field

Abstract: With a wide range of composite resins available today, clinicians can benefit from knowledge of the infrastructure of a particular material in order to determine which type will work best in a specific clinical situation. The purpose of this study is to analyze the biomechanical behavior of four types of composite resins, two of them used in direct restorations and the other two for prosthetic restorations created in the lab.The deformations, hardness and elasticity were analyzed under the same condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
1
7
0
7
Order By: Relevance
“…Surprisingly, and also according to other studies in the literature, the results of the present study showed that the method of reinforcing devitalized endodontically treated teeth with glass fiber posts does not increase their resistance to fracture, on the contrary, it decreases it [37][38][39]. Several factors may be incriminated, such as: the poor adhesion to radicular dentin, the method of cement application into the root canal and around the fiber post [40], the way of conditioning the surface of the fiber post [41][42][43] and the need to use more materials and coupling agents between them than in restorative techniques using fiberglass reinforced composite.…”
Section: Discussionsupporting
confidence: 79%
“…Surprisingly, and also according to other studies in the literature, the results of the present study showed that the method of reinforcing devitalized endodontically treated teeth with glass fiber posts does not increase their resistance to fracture, on the contrary, it decreases it [37][38][39]. Several factors may be incriminated, such as: the poor adhesion to radicular dentin, the method of cement application into the root canal and around the fiber post [40], the way of conditioning the surface of the fiber post [41][42][43] and the need to use more materials and coupling agents between them than in restorative techniques using fiberglass reinforced composite.…”
Section: Discussionsupporting
confidence: 79%
“…Among the most used resins in dental materials are the epoxy systems [12], bisphenol A-glycidyl methacrylate (Bis-GMA) [13], urethane-dimethacrylate (UDMA) [14], triethylene glycol dimethacrylate (TEGDMA) [15]. These resins are well known for their lower price, compared to porcelains, and reliable potential in making medical-related products especially on account of the suitable properties of resistance to abrasion, moderate polishing requirements and manageable shrinkage [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of using resins in dental implantology is at a mature stage, with good potential in making products, such as prosthesis bases, artificial teeth, temporary prostheses, gutters, sealants, etc., due to the satisfactory properties of abrasion resistance, light polishing, minimum shrinkage [9,10] and compatibility with the tissues on which it aggregates [11].…”
Section: Introductionmentioning
confidence: 99%
“…In bioengineering, the use of nanoparticles in common products has been studied for almost 30 years [9], proving an excellent potential in covering gaps in research into new materials for dental reconstructions. Nano-additives, in particulate form, are incorporated into composite dental resins to provide restorative properties closely identical to a natural tooth, such as strength, appearance and adherence, also [11].…”
Section: Introductionmentioning
confidence: 99%